The transposon-like correia elements encode numerous strong promoters and provide a potential new mechanism for phase variation in the meningococcus - Siddique, Azeem; Buisine, Nicolas; Chalmers, Ronald (Public Library of Science, 2011)
Neisseria meningitidis is the primary causative agent of bacterial meningitis. The genome is rich in repetitive DNA and almost 2% is occupied by a diminutive transposon called the Correia element. Here we report a bioinformatic analysis defining eight subtypes of the element with four distinct types of ends. Transcriptional analysis, using PCR and a lacZ reporter system, revealed that two ends in particular encode strong promoters. The activity of the strongest promoter is dictated by a recurrent polymorphism (Y128) at the right end of the element. We highlight examples of elements that appear to drive transcription of adjacent genes and others that may express small non-coding RNAs. Pair-wise comparisons between three meningococcal genomes revealed that no more than two-thirds of Correia elements maintain their subtype at any particular locus. This is due to recombinational class switching between elements in a single strain. Upon switching subtype, a new allele is available to spread through the population by natural transformation. This process may represent a hitherto unrecognized mechanism for phase variation in the meningococcus. We conclude that the strain-to-strain variability of the Correia elements, and the large number of strong promoters encoded by them, allows for potentially widespread effects within the population as a whole. By defining the strength of the promoters encoded by the eight subtypes of Correia ends, we provide a resource that allows the transcriptional effects of a particular subtype at a given locus to be predicted.